The social world of adolescents: international perspectives - Hurrelmann, Klaus; Engel, Uwe (Prävention und Intervention im Kindes- und Jugendalter, 1989)
The social world of adolescents : a sociological perspective / Klaus Hurrelmann -- Individualization as hope and as disaster : a socioeconomic perspective / Martin Baethge -- The focal theory of adolescence : a psychological perspective / John C. Coleman -- The lifeworld of young people : a systems-theoretical perspective / Donato Palazzo -- Adolescent transitions : a life-course perspective / Millicent E. Poole -- The world of higher education : a socialization-theoretical perspective / John C. Weidman -- Adolescents as productive processors of reality : methodological perspectives / Klaus Hurrelmann -- Mentors in adolescents' lives / Stephen F. Hamilton, Nancy Darling -- The significant people in the social networks of adolescents / Inge B(c)œ -- Parental and peer support in adolescence / Wim Meeus -- Working mothers and the educational achievements of their children / Jaap Dronkers -- Significant partners in childhood and adolescence / Sei Matsuda --